국내환경에서 밀 유전자원의 연차간 농업특성 분석 - 손재한; Jae-han Son; 양진우; Jinwoo Yang; 강천식; Chon-sik Kang; 김경훈; Kyeong-hoon Kim; 김경민; Kyeong-min Kim; 정한용; Han-yong Jeong; et al. (Korean journal of crop science, 2021)
Securing a range of wheat resources is of particular importance with respect to wheat breeding, as it provides a broad genetic foundation. Although wheat breeders have used different wheat germplasms as material resources in current breeding systems, the traits of most germplasms collected from foreign countries differ from the unique traits that have evolved in the Korean environment. In this study, conducted over a 2-year period (2018 and 2019), we therefore evaluated the agricultural traits 1,967 wheat germplasms collected not only in Korea but also worldwide. During the period from sowing to February, the average temperature in 2019 was greater than 1°C, whereas from March to June, the average temperature was approximately 0.9°C higher in 2018. Compared with the growth recorded in 2018, the stem length in 2019 increased by approximately 20 cm in 2019, and there were notable differences heading date and maturation between 2018 and 2019. In 2019, the heading dates of 973 and 713 wheat resources were earlier and later than those in 2018, respectively. Moreover, stem length was found to be highly correlated with the heading date and maturation. In Korea, where the rainy season and tine of rice transplantation overlap with the time of wheat harvest, early flowering time with high grain yield has been the most important selection target with respect to wheat breeding. We anticipate that the findings of this study will provide would use a foundation for the selection of elite materials and the development of resource core-sets for Korean wheat breeding programs.